Application of Becton Dickinson FACSTM Combinatorial Antibody Profile (FACSTM CAP) technology to the identification of efficiency of tuberculosis therapy - Smith, Bronwyn Kerry (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015